Передумови становлення Панфильської дослідної станції та організаційна й наукова діяльність М. Н. Шевченка в установі у 1930-х роках - Чередник, К. П. (НТУ "ХПІ", 2014)
Розглядаються передумови створення Панфильської дослідної станції. Аналізуються роботи з цього приводу вчених, в яких започатковано і зроблено значне підґрунтя для розгортання повноцінної наукової діяльності установи. Доведено історично-вирішальну роль третього її директора М. Н. Шевченка. Показано вагомі здобутки установи започатковані в 1930-х роках, що стали класичними для землеробства на родючих торфових ґрунтах.

Background of becoming Panfyly Experimental Station is observed. Scientists’ works on this subject that initiated and made a significant basis for the deployment of full scientific activity are analyzed. Based on the conclusions of scientific expeditions, the study of climatic, economic and other relevant factors the importance of agricultural uses of wetlands has been brought to authorities. Establishment of the institution has become an important government decisions. Historically decisive role of the third of its director M.N. Shevchenko is proved. Significant achievements of the institution under the leadership of the scientist, started in 1930 and became a classic for agriculture in the fertile peaty soils, are shown.
Background of becoming Panfyly experimental station and organizational and scientific activity of M. N. Shevchenko in the institution in 1930-ies.
Keywords: болотні грунти; історія; сільськогосподарська наука; Mykola Nychyporovych Shevchenko; history; agricultural science